KONSELING TRAUMATIK Pendekatan Cognitif-Behavior Therapy - ETTY SETIAWATI (Al-Tazkiah : Jurnal Bimbingan dan Konseling Islam, 2016)
ndonesia is one of the countries that are frequently hit by natural disasters, and not a few of the consequences of such natural disasters in?ict many victims. Moreover, many of the survivors suffered psychological trauma. Departing from that fact, the government should prepare individuals who are skilled in dealing with the traumatic case that experienced by the victims of natural disasters. Trauma is an emotional condition expanded after the inconvenience traumatic event, sadden, frightening, worrying, disappointing, such as rape, combat, physical violence, accidents, natural disasters, and the certain events that make the inner counselee depressed. Counseling in traumatic case refers to a therapeutic help are directed to change the attitudes and behavior of the traumatic counselee. Carried out face to face between counselee and counselor; through interview techniques with the counselee so that the problem about what they have experienced will be resolved. One of therapy approaches can be applied by professional counselors is Cognitive Behavior Therapy (CBT). Aaron T. Beck defnes CBT is the counseling approach that is designed to resolve the counselee problem at this time by doing cognitive restructuration and behavior deviant. CBT undertaken with cognitive restructuration and exposure.